Veno-venous extracorporeal membrane oxygenation in patient with acute respiratory distress syndrome - Mohamed Yosri Mohamed Ahmed; Akram Mohamed Abdelbary; Alia Hassan Abdelfattah; Mohamed Mohamed Khaled (Cairo : Mohamed Yosri Mohamed Ahmed, 2018)
Introduction: Extracorporeal membrane oxygenation (ECMO) is considered a rescue therapy in severe cases of acute respiratory failure. Aim of the work: Test the clinical impact on in-hospital patient course regarding morbidity and mortality using the extracorporeal membrane oxygenation (ECMO) as a salvage therapy for patient with severe ARDS. Methods: Our ECMO program started in January 2014. Since then we supported 23 respiratory failure patients on ECMO indicated according to ELSO guidelines, Respiratory failure patients were subjected to VV ECMO when lung injury score (LIS) was above 3 and PaO2/FiO2 <100 on protective lung strategy mechanical ventilation according to ARDS net protocol and or severe hypercapnia with pH <7.2 with trial of prone positioningin the indicated cases. Percutaneous cannulation was done in all patients using single lumen cannulae, additional cannula was added when needed. Cardiohelp (maquet, germany) and rotaflow (maquet, Germany) ECMO consoles were used with centrifugal pump. ECMO circuits PLS for rotaflow and HLS for cardiohelp were changed when indicated
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Acute respiratory distress syndrome; Extracorporeal membrane oxygenation (ECMO); Veno-venous extracorporeal membrane oxygenation